2016
DOI: 10.2967/jnumed.115.170456
|View full text |Cite
|
Sign up to set email alerts
|

Initial Results of a Prospective Clinical Trial of 18F-Fluciclovine PET/CT in Newly Diagnosed Invasive Ductal and Invasive Lobular Breast Cancers

Abstract: 18 F-labeled 1-amino-3-fluorocyclobutane-1-carboxylic acid ( 18 Ffluciclovine) is a leucine analog PET/CT radiotracer that depicts amino acid transport into cells. Amino acid transport proteins have been shown to be upregulated in breast malignancies by microarray and immunohistochemical analysis, so we hypothesized that 18 Ffluciclovine may provide a novel method of visualizing breast cancer and now report a prospective clinical trial of 18 F-fluciclovine PET/CT in newly diagnosed advanced local invasive duct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 23 publications
1
50
0
Order By: Relevance
“…Therefore, the development of better metabolic imaging agents for ILC could be clinically valuable. There is preliminary evidence that ILC may be more 18 F-fluciclovineavid than 18 F-FDG-avid (7,8). This study included 6 patients with ILC tumors, all of which were 18 F-fluciclovine-avid.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the development of better metabolic imaging agents for ILC could be clinically valuable. There is preliminary evidence that ILC may be more 18 F-fluciclovineavid than 18 F-FDG-avid (7,8). This study included 6 patients with ILC tumors, all of which were 18 F-fluciclovine-avid.…”
Section: Discussionmentioning
confidence: 99%
“…18 F-labeled 1-amino-3-fluorocyclobutane-1-carboxylic acid ( 18 F-fluciclovine), an amino acid analog labeled with the positron emitter 18 F, is under investigation as an imaging agent for several types of malignancy (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12). 18 F-fluciclovine was recently approved by the U.S. Food and Drug Administration for the detection of recurrent prostate cancer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because amino acid transport is upregulated in many types of cancer, 18 F-fluciclovine has potential application in multiple types of cancer. In this issue of The Journal of Nuclear Medicine, 2 groups report promising preliminary results for FACBC in women with breast cancer naïve to therapy (2,3). These studies demonstrated substantially higher uptake of 18 F-fluciclovine in primary and metastatic breast cancers than in benign breast lesions and normal breast tissue.…”
mentioning
confidence: 87%
“…Approval was granted to 18F-fluciclovine (trade name: Axumin) in May 2016 for the clinical indication of suspected prostate cancer recurrence based on elevated PSA levels following prior treatment and has Medicare pass through reimbursement effective January 2017. It should be noted that 18F-fluciclovine has been studied to image other malignancies such as breast (14) and glioma (15) but discussion of these applications is beyond the scope of this article.…”
Section: Introductionmentioning
confidence: 99%